Glycine Transporter 2: Mechanism and Allosteric Modulation - Frangos, Zachary J.; Cantwell Chater, Ryan P.; Vandenberg, Robert J. (Frontiers in Molecular Biosciences, 2021)
Neurotransmitter sodium symporters (NSS) are a subfamily of SLC6 transporters responsible for regulating neurotransmitter signalling. They are a major target for psychoactive substances including antidepressants and drugs of abuse, prompting substantial research into their modulation and structure-function dynamics. Recently, a series of allosteric transport inhibitors have been identified, which may reduce side effect profiles, compared to orthosteric inhibitors. Allosteric inhibitors are also likely to provide different clearance kinetics compared to competitive inhibitors and potentially better clinical outcomes. Crystal structures and homology models have identified several allosteric modulatory sites on NSS including the vestibule allosteric site (VAS), lipid allosteric site (LAS) and cholesterol binding site (CHOL1). Whilst the architecture of eukaryotic NSS is generally well conserved there are differences in regions that form the VAS, LAS and CHOL1.Here, we describe ligand-protein interactions that stabilize binding in each allosteric site and explore how differences between transporters could be exploited to generate NSS specific compounds with an emphasis on GlyT2 modulation.